A Case of Small Bowel Obstruction Caused by Bezoars Diagnosed with Double Balloon Enteroscopy. (15th February 2012) - Saita, Masayuki; Maekawa, Hiroshi; Sato, Koichi; Orita, Hajime; Sakurada, Mutsumi; Ito, Tomoaki; Sinjoh, Kunihiro; Komatsu, Yoshihiro; Nohara, Shigeo
Abstract : Primary small bowel bezoars are rare and cause acute abdomen due to small bowel obstruction (SBO). A 69-year-old Japanese man presented with epigastric pain associated with fullness. Physical examination of the abdomen showed no marked signs of peritoneal irritation. An erect X-ray film of the abdomen showed small bowel obstruction. Computed tomography (CT) showed a dilated small bowel loop proximal to the site of the obstruction. Retrograde double balloon enteroscopy (DBE) was performed and showed yellow, hard bezoars blocking the distal ileum. At surgery, a bezoar was found impacted in the distal ileum, and enterotomy with extraction was performed. After 9 days, the patient was discharged from our hospital in satisfactory condition. DBE also appears to be a safe and useful diagnostic tool in patients with SBO, and the findings of DBE influence the strategy of therapy in patients in whom the cause of SBO could not be determined by conventional radiography.